2021
DOI: 10.1158/1078-0432.ccr-21-1200
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Tissue TCR Repertoire Evenness Is Associated with Complete Pathologic Response in Patients with NSCLC Receiving Neoadjuvant Chemoimmunotherapy

Abstract: Characterization of the T-cell receptor (TCR) repertoire may be a promising source for predictive biomarkers of pathological response to immunotherapy in locally-advanced nonsmall cell lung cancer (NSCLC).Experimental Design: In this study, next-generation TCR sequencing was performed in peripheral blood and tissue samples of 40 NSCLC patients, before and after neoadjuvant chemoimmunotherapy (NADIM clinical trial, NCT03081689), considering their complete pathologic response (CPR) or non-CPR. Beyond TCR metrics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
(51 reference statements)
4
39
1
Order By: Relevance
“…In addition, responders for PD-1 blockade therapy showed a higher total frequency of blood-tumor overlapping clones in the blood before treatment (44), a greater number of blood-tumor overlapping clones after treatment (32), and more pronounced expansion of blood-tumor overlapping clones in the blood after treatment (45). Similar observations were reported for neoadjuvant chemoimmunotherapy (28) and clinical trial of a humanized anti-CD4 antibody (46,48). The association between the blood-tumor overlapping repertoire in the tumor and clinical responses has also been analyzed.…”
Section: Blood-tumor Overlapping Repertoire Analysissupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, responders for PD-1 blockade therapy showed a higher total frequency of blood-tumor overlapping clones in the blood before treatment (44), a greater number of blood-tumor overlapping clones after treatment (32), and more pronounced expansion of blood-tumor overlapping clones in the blood after treatment (45). Similar observations were reported for neoadjuvant chemoimmunotherapy (28) and clinical trial of a humanized anti-CD4 antibody (46,48). The association between the blood-tumor overlapping repertoire in the tumor and clinical responses has also been analyzed.…”
Section: Blood-tumor Overlapping Repertoire Analysissupporting
confidence: 72%
“…A clinical study on anti-PD-1 antibody therapy in melanoma patients showed that the clonality of the TCR repertoire in the tumor before treatment was higher in responders than in nonresponders (23)(24)(25)(26). Similarly, the total frequency of the top 1% clones in tumor repertoire was greater in responders than in non-responders in studies on neoadjuvant immunotherapy in patients with non-small cell lung cancer (NSCLC) (27,28). Furthermore, responders showed more T-cell clones with increased frequency (23) and increased clonality of the T-cell repertoire (29) in the tumor after treatment.…”
Section: Tcr Repertoire Analysis In Tumor Immunology: Achievements and Challengesmentioning
confidence: 99%
“…Responders also had more stable pools of nonspecific stimulus during treatment (Figure 6C). These findings support the notion that prognoses are most favorable when ICB induces focused, oligoclonal responses against highly clonal neoantigens, at least for certain tumor types [21], [40].…”
Section: Ctl Dynamics Correlate With Icb Response and Immunoeditingsupporting
confidence: 83%
“…In this study, the clonal space in the peripheral blood of the top 1% of clones in pretreatment tissue samples was significantly reduced in patients with cPR, and no significant reductions were observed in patients without cPR. Interestingly, comparing the immune gene expression profile of pretreatment samples from patients with a high and low top 1% clonal space, several immune gene signatures such as Interferon gamma and IL2 were differentially expressed, suggesting that this biomarker can be used to predict response to therapy and to evaluate tumor immunogenicity [ 94 ].…”
Section: Biomarkers For Potential Use As Predictors Of Neoadjuvant Im...mentioning
confidence: 99%